Congenital Herpes Simplex Virus Infection - DALGIÇ, Nazan (Cerrahpaşa Medical Journal, 2014)
Neonatal herpes simplex virus (HSV) infection can result in serious morbidity and mortality. Neonatal HSV infection usually is acquired during the birth process, as the neonate comes in contact with the virus during passage through an infected canal. After an incubation period which can last as long as 2 to 4 weeks, neonatal HSV disease then manifests in 1 of 3 ways: (1) disseminated disease, with visceral organ involvement; (2) central nervous system disease; or (3) disease limited to the skin, eyes, and/or mouth. The diagnosis of neonatal HSV can be difficult, but it should be suspected in any newborn with irritability, lethargy, fever or poor feeding at one week of age. Diagnosis is made by culturing the blood, cerebrospinal fluid, urine and fluid from eyes, nose and mucous membrans. Treatment of neonatal HSV disease with intravenous acyclovir has improved the likelihood of survival substantially, although neurologic morbidity remains common sequelae, especially among survivors of central nervous system disease. The surest way to improve outcomes rapidly at this point is to raise awareness of neonatal HSV disease, resulting in the establishment of earlier diagnoses and more rapid institution of antiviral therapy.